Clinical Performance of Human Papillomavirus Testing and Visual Inspection With Acetic Acid in Primary, Combination, and Sequential Cervical Cancer Screening in China. Issue 8 (August 2019) - Wang, Margaret Z.; Feng, Rui-mei; Wang, Shaoming; Duan, Xian-zhi; Li, Dong; Zhang, Xun; Mu, Rong; Qiao, Youlin; Smith, Jennifer S.
Abstract : Background: World Health Organization guidelines recommend screening with human papillomavirus (HPV) testing followed by either treatment of all HPV-positives, or by visual inspection (VIA) for triage to treatment, citing insufficient evidence to recommend either strategy over the other. Methods: We assessed VIA and HPV testing individually, in combination (HPV-VIA cotesting), and as triage models. Three thousand women were screened in Inner Mongolia, China, concurrently with HPV testing and VIA in a real population setting. Screen-positive women underwent colposcopy, and biopsy, if indicated. Accuracy of screening algorithms for cervical intraepithelial neoplasia grade 2 or higher (CIN-2+) was calculated after controlling for verification bias. HPV testing followed by VIA triage for CIN-2+ detection was compared with Hybrid Capture 2 viral loads triage, measured in relative light units/cutoff. Results: CIN-2+ prevalence was 1.0%. Corrected sensitivity, false negative rate, and specificity for CIN-2+, respectively, for primary HPV testing were 89.7%, 10.3%, and 83.3%; 44.8%, 55.2%, and 92·3% for VIA; 93.1%, 6.9%, and 80.2% for HPV-VIA cotesting; and 41.4%, 58.6, and 95.4% for HPV with VIA triage scenarios. Using relative light units/cutoff of 5 or greater to triage HPV-positive women had twice the sensitivity as VIA triage, with comparable specificity for CIN-2+. Conclusions: When VIA performs relatively poorly and HPV testing is available, adding VIA to sequential (ie, HPV followed by VIA triage) or primary (HPV-VIA cotesting) screening does not significantly improve CIN-2+ detection beyond primary HPV screening alone. Sequential screening (ie, HPV followed by VIA triage) reduces sensitivity too low for population-based screening programs. The HPV viral loads could offer an alternative low-resource country triage strategy. Abstract : Sequential algorithms of primary human papillomavirus with visual inspection (VIA) triage did not have better clinical performance than primary human papillomavirus or primary VIA alone in low-resource settings where VIA sensitivity is relatively low.